2015
DOI: 10.1007/s00167-015-3744-z
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic balance deficits in individuals with chronic ankle instability compared to ankle sprain copers 1 year after a first-time lateral ankle sprain injury

Abstract: lateral ankle sprain copers, 1-year following a first-time lateral ankle sprain injury. AbstractPurpose: To quantify the dynamic balance deficits that characterize a group with chronic ankle instability compared to lateral ankle sprain copers and non-injured controls using kinematic and kinetic outcomes.Methods: Forty-two participants with chronic ankle instability and twenty-eight ankle sprain copers were initially recruited within 2-weeks of sustaining a first-time, acute lateral ankle sprain and required to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
53
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 39 publications
(97 reference statements)
4
53
1
2
Order By: Relevance
“…11 One such task that involves muscles throughout the lower extremity is the modified Star Excursion Balance Test, otherwise known as the Y-Balance Test (YBT). This clinical tool is commonly used to assess sensorimotor adaptations, and multiple researchers 12,13 have suggested that individuals with CAI present with impairments in YBT performance. This task involves multiple lower extremity structures for successful performance and specifically requires dynamic single-limb stabilization while participants maintain a semi-squatting position and reach outside the base of support in the anterior, posteromedial, and posterolateral directions.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…11 One such task that involves muscles throughout the lower extremity is the modified Star Excursion Balance Test, otherwise known as the Y-Balance Test (YBT). This clinical tool is commonly used to assess sensorimotor adaptations, and multiple researchers 12,13 have suggested that individuals with CAI present with impairments in YBT performance. This task involves multiple lower extremity structures for successful performance and specifically requires dynamic single-limb stabilization while participants maintain a semi-squatting position and reach outside the base of support in the anterior, posteromedial, and posterolateral directions.…”
mentioning
confidence: 99%
“…Alterations in hip kinematics, 13 hip-muscle fatigue, 16,17 and decreased hip-extension strength 18,19 have been identified and shown to be related to decreased YBT performance, particularly in the posterior-reach directions. Although all of these aspects have been explored, little information is available about the functional-activation patterns of the gluteal muscles during the YBT as they influence task performance in the population with CAI.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Between 50% and 70% of the people who sustain an LAS will develop chronic ankle instability (CAI), a condition characterized by lingering pain, instability, injury recurrence, and persistent functional disability. 3 Chronic symptoms and reinjury have been shown to occur rapidly, with recent authors [4][5][6][7][8] demonstrating the onset of CAI symptoms as early as 6 to 12 months after the initial acute LAS. The steps for determining the status of an LAS through clinical examination are well established and can be supplemented with advanced imaging.…”
mentioning
confidence: 99%
“…Thus, clinicians often rely on subjective visual observations of the individuals’ “steadiness” while completing the task. As a result, there is potential that these traditional measures of dynamic balance may not capture subtle sensorimotor deficits possessed by individuals with conditions such as acute lateral ankle sprain [1], chronic ankle instability [12], and concussion [13, 14]. …”
Section: Introductionmentioning
confidence: 99%